2022
DOI: 10.7759/cureus.21068
|View full text |Cite
|
Sign up to set email alerts
|

Fruitful Pregnancy Outcome in a Case of Eisenmenger Syndrome With Severe Pulmonary Hypertension: A Rare Case Report

Abstract: Eisenmenger syndrome (ES) is considered an absolute contraindication for pregnancy. ES is characterized by a congenital heart abnormality that results in a significant anatomical shunt. Hemodynamic forces generate a left-right shunt, leading to severe pulmonary arterial hypertension (PAH). Eventually, the shunt will become a right-to-left shunt due to increased pulmonary vascular resistance, leading to significant hypoxemia and cyanosis. Pregnant women with ES experience volume overload as a result of the synd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…The literature review identified 72 cases of pregnancies with ES from 11 studies conducted between 2003 and 2022 (Table 4). [11][12][13][14][15][16][17][18][19][20][21] Among these cases, 30.5% involved pretricuspid shunts, more than half (56.9%) involved posttricuspid shunts, and the rest involved complex CHD or unknown defect types. In addition, 63.8% of the pregnant women delivered by caesarean section.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The literature review identified 72 cases of pregnancies with ES from 11 studies conducted between 2003 and 2022 (Table 4). [11][12][13][14][15][16][17][18][19][20][21] Among these cases, 30.5% involved pretricuspid shunts, more than half (56.9%) involved posttricuspid shunts, and the rest involved complex CHD or unknown defect types. In addition, 63.8% of the pregnant women delivered by caesarean section.…”
Section: Literature Reviewmentioning
confidence: 99%